KONSEP THE LEADER’S INNER JORNEY DALAM MENINGKATKAN KUALITAS DAKWAH: STUDI KOMPARATIF PEMIKIRAN BUYA HAMKA - Nur Fitriah; Naila Marissa; Alfi Nur Chasifah (Bayan lin-Naas : Jurnal Dakwah Islam, 2026)
This study aims to analyze the concept of the leader’s inner journey in improving the quality of da'wah through a comparative study of Buya Hamka’s thought. The primary focus lies in exploring the internal dimensions of leadership, including spirituality, moral integrity, self awareness, and emotional maturity, as determinants of effective da'wah practices. This research employs a descriptive qualitative approach, utilizing library research techniquesby examining Buya Hamka’s works such as books, tafsir, and relevant writings on leadership and da'wah. The data analysis is conducted interpretatively, emphasizing a conceptual comparison between the inner journey framework in contemporary leadership discourse and the values embedded in Buya Hamka’s perspective. The findings reveal that the concept of an inner journey in Buya Hamka’s thought strongly emphasizes tazkiyatun nafs (self-purification), sincerity, and exemplary conduct as the foundational elements of effective da'wah. Furthermore, there is a significant alignment between the inner journey concept and Islamic leadership principles that prioritize character development and spiritual strengthening as sources of moral authority in da'wah. The implication of this study suggests that the quality of da'wah is not solely determined by rhetorical skills but also by the depth of spirituality and personal integrity of a da’i as a leader of the community. Keywords: inner journey, leadership, da'wah, Buya Hamka, spirituality.